2021
DOI: 10.1016/j.jval.2020.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Estimating a Preference-Based Index for Mental Health From the Recovering Quality of Life Measure: Valuation of Recovering Quality of Life Utility Index

Abstract: Background: There are increasing concerns about the appropriateness of generic preference-based measures to capture health benefits in the area of mental health. Objectives: The aim of this study is to estimate preference weights for a new measure, Recovering Quality of Life (ReQoL-10), to better capture the benefits of mental healthcare. Methods: Psychometric analyses of a larger sample of mental health service users (n = 4266) using confirmatory factor analyses and item response theory were used to derive a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…One important quality of life instrument, specifically designed for use in the mental health field, that has become available since the completion of our review is the Recovering Quality of Life (ReQoL) measure [ 60 ]. The ReQoL measure is a preference-based [ 61 ] patient reported outcome measure that was explicitly designed to cover all seven dimensions of the evaluation framework used in the current study. The development of the ReQoL measure highlights the need and search for outcome instruments that adequately measure and value the benefits of mental healthcare interventions.…”
Section: Discussionmentioning
confidence: 99%
“…One important quality of life instrument, specifically designed for use in the mental health field, that has become available since the completion of our review is the Recovering Quality of Life (ReQoL) measure [ 60 ]. The ReQoL measure is a preference-based [ 61 ] patient reported outcome measure that was explicitly designed to cover all seven dimensions of the evaluation framework used in the current study. The development of the ReQoL measure highlights the need and search for outcome instruments that adequately measure and value the benefits of mental healthcare interventions.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was not unexpected because a great number of studies have confirmed the good performance of the EQ-5D-5L in HK Chinese population [ 34 37 ]. However, no empirical evidence about the other two measures in HK population was found, especially that this is the first paper using the ReQoL-UI in the HK population [ 15 ]. Additionally, the ICECAP-A and EQ-5D-5L exhibited acceptable to good test–retest reliability but the ICC for the ReQoL-UI was poor.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of HK specific preference weights, we used the UK preference weights to calculate the utility score in this study. The weights were estimated from a sample of 305 UK general population using the time trade-off method [ 15 ]. The ReQoL-UI utility score ranges between −0.195 and 1, which reflects people’s worst and best recovered HRQoL, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results may be useful for service system planners in helping to prioritise which measures should be included in routine data collection. Although direct measurement of health utility with measures such as the ReQoL [29] may be feasible in some mental health services, relying on clinical measures that can also map to health utility may be an attractive alternative.…”
Section: Discussionmentioning
confidence: 99%